THE APPLICATION OF DRIP IRRIGATION SYSTEM ON CAULIFLOWER (Brassica Oleracea Var. Botrytis L. Subvar. Cauliflora DC) IN AGREENHOUSE - Hendri - Yanto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
The research aimed to test performance of a drip irrigation system to irrigate cauliflower cultivated in a greenhouse.  The drip irrigation system using emitter type regulating stick emitter as many 315.  One Main pipe, one manifold, and four lateral pipes were from PE types with the diameter of 13 mm.  The methods to deliver irrigation water were by using a small pump 13 Watt and by using gravitational pressure with head 155 cm. Variables observed were emission uniformity (EU), water requirement, plant growth, and water productivity.  The results showed that   Emission uniformities were 64,49 % for gravitational flow and 61,46 % for pumping flow.  These values were still below recommended, that is 75 % - 85 %. The minimum, maximum, and mean reference evapotranspiration (ETo) were recorded as 5,80 mm/day, 9,70 mm/day, and 7,20 mm/day.  Whilst crop evapotranspiration (ETc) at the day of 41 after planted was 3.2 mm/day.  Average yield of cauliflower was 58 gram per plant, while water productivity was 0,87 gram/litter.Keyword:     cauliflower, crop water requirement, drip irrigation, emitter, emission uniformity